The Analysis of the Implementation of EMS ISO 14001:2015 Based on the Global Environmental Management Initiative at PT Pertamina Hulu Rokan Zone I Pangkalan Susu Field - Fattahillah Harahap; Muhammad Zakaria (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This research aims to analyze the implementation of the ISO 14001:2015 Environmental Management System at PT Pertamina Hulu Rokan Zone 1 Pangkalan Susu Field using the Global Environmental Management Initiative (GEMI) method. Evaluation was carried out using the GEMI checklist which includes the 7 main clauses of ISO 14001:2015 and GAP analysis. Data collection was carried out for 1 month through observation, interviews and assessments. The research results show that the implementation of the environmental management system in companies reached an average of 85.9%, with details: organizational context clause (85%), leadership (89.4%), planning (84.2%), support (78, 9%), operations (88.4%), performance evaluation (86.7%), and improvement (88.8%). Overall, the implementation of the environmental management system at PT Pertamina Hulu Rokan Zone 1 Pangkalan Susu Field is included in the good category, although there are still several aspects that require improvement, especially the support clause which received the lowest score.